2000
DOI: 10.1159/000008141
|View full text |Cite
|
Sign up to set email alerts
|

Type I Sialidosis: A Clinical, Biochemical and Neuroradiological Study

Abstract: We report biochemical, morphological and neuroradiological findings in a 40-year-old woman affected with type I sialidosis. The clinical symptoms, consisting of a cerebellar syndrome, were first noted at the age of 17 years. The macular cherry-red spot was first observed after 23 years of disease. A CT scan performed at 21 years of age showed enlargement of the fourth ventricle. Nuclear magnetic resonance imaging of the brain performed at the age of 40 showed severe atrophy of the cerebellum and pontine region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 14 publications
(16 reference statements)
1
25
0
3
Order By: Relevance
“…Based on the clinical findings of our patient and the biological properties of the second mutation (p.P80L), the novel p.D135N mutation was considered to be associated with a relatively mild clinical phenotype of sialidosis (sialidosis type I). Diffuse brain atrophy is commonly observed in the advanced stage of sialidosis type I; however, the results of neuroradiological imaging can be normal on the first examination in affected patients (19,20,(27)(28)(29). There have been very few studies regarding long-term changes in the findings of neuroimaging (20,29), and it is largely unknown how rapidly brain atrophy progresses in patients with sialidosis type I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the clinical findings of our patient and the biological properties of the second mutation (p.P80L), the novel p.D135N mutation was considered to be associated with a relatively mild clinical phenotype of sialidosis (sialidosis type I). Diffuse brain atrophy is commonly observed in the advanced stage of sialidosis type I; however, the results of neuroradiological imaging can be normal on the first examination in affected patients (19,20,(27)(28)(29). There have been very few studies regarding long-term changes in the findings of neuroimaging (20,29), and it is largely unknown how rapidly brain atrophy progresses in patients with sialidosis type I.…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse brain atrophy is commonly observed in the advanced stage of sialidosis type I; however, the results of neuroradiological imaging can be normal on the first examination in affected patients (19,20,(27)(28)(29). There have been very few studies regarding long-term changes in the findings of neuroimaging (20,29), and it is largely unknown how rapidly brain atrophy progresses in patients with sialidosis type I. Chen et al (19) reported the results of a long-term follow-up study of sialidosis type I siblings homozygous for the p.S182G missense mutation.…”
Section: Discussionmentioning
confidence: 99%
“…29 There are two subtypes, with Type 1 manifesting during childhood or juvenile ages. 33 Individuals with Type 1, also known as cherry red spot myoclonus syndrome, have macular cherry red spots, myoclonic epilepsy, progressive loss of vision and ataxia.…”
Section: 28mentioning
confidence: 99%
“…34 The congenital form is associated with nonimmune hydrops fetalis and ascites. 33,34 The infantile form may have similar features to MPS I, including dysostosis multiplex (Figure 9), coarse facies, visceromegaly and developmental delay, but may develop macular cherry red spots in contrast to MPS I.…”
mentioning
confidence: 99%
“…There are also signs of pyramidal liberation and ataxia. Its evolution is slow, without mental deterioration [51,52].…”
Section: Sialidosismentioning
confidence: 99%